Comparing the biogeochemical functioning of two arid subtropical coastal lagoons: the effect of wastewater discharges - Julio Medina-Galván (Taylor & Francis Group, 2021)
Nutrient flux, net metabolism, and N2 fixation and denitrification processes were estimated and compared in two semi-arid subtropical coastal lagoons in the Gulf of California: El Soldado (ES), where no wastewater is discharged, and El Rancho (ER), where shrimp farm effluents are regularly discharged. Biogeochemical processes were evaluated with the LOICZ model. Flushing time was <2 days in both systems. Nutrient fluxes were higher in ER than in ES and both systems acted as nutrient sinks for most of the year. ER showed a larger nutrient flow rate in the summer and autumn due to the input of shrimp-farm effluents. Nitrogen fluxes increased in both ER and ES in the winter in response to the increased nutrient supply from coastal upwellings. ER and ES both showed autotrophic metabolism and N2 fixation in the spring, autumn, and winter, but heterotrophic metabolism and denitrification in the summer. Denitrification dominated in ER (−2.21 mmol m2 day−1) and values were higher than those estimated in ES (−0.45 mmol m2 day−1). The comparative analysis between ES and ER evidenced the significant changes in its biogeochemical performance caused by the input of anthropogenic nutrients, and can orient the environmental management of coastal lagoons.